ANALYSIS OF SEMANTIC EXTENSIONS IN INDONESIAN CELEBGRAM’S INSTAGRAM COMMENTS - Faradiba, Fadya (Journal of Language, Literature and Teaching, 2023)
AbstractThe number of Indonesians using social media is rising yearly. This article attempts to study the usage of language associated with semantic extensions in comments left by internet users on the Instagram account of Karin Novilda, also known as Awkarin (@narinkovilda), one of the Instagram influencers or celebrities. It uses a descriptive qualitative approach. The findings demonstrated that semantic expansions took place in internet users' remarks on the celebgram's Instagram account. This expansion of meaning is probably due to technological advancements and the quickening pace of life. Language users that utilize the internet are also impacted by the world around them. The growth of meaning further demonstrates that language is in fact static and not dynamic. Language has a number of advantages, including the ability to live and develop continually as long as its users continue to use it, and the ability to change its meaning at the user's discretion. In other words, there are no constraints on the language, allowing it to grow and alter to meet the demands of its users. Another concrete example of how language is arbitrarily constructed and how it develops is the phenomena of meaning extension.Keyword: Instagram, Semantic, Extension.